2011
DOI: 10.1038/gt.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment in skin gene therapy: viral–cellular fusion transcripts generated by proviral transcriptional read-through in keratinocytes transduced with self-inactivating lentiviral vectors

Abstract: Cutaneous gene therapy can be envisioned through the use of keratinocyte stem cell clones in which retroviral genotoxic risks can be pre-assessed. While transactivation of cellular genes by the retroviral long terminal repeat enhancer has been proven in experimental and clinical settings, the formation of chimeric viral-cellular transcripts originated by the inefficient termination (read-through) of retroviral transcripts remains to be studied in depth. We now demonstrate the widespread presence of viral-cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
(26 reference statements)
1
40
1
Order By: Relevance
“…They also found that the presence of a wild-type LTR increased the incidence of aberrant splicing, but since Mavilio and colleagues performed all of their analyses with SIN lentiviral vectors, this nuance gives no real comfort. These findings mirror the recent report of proviral transcriptional read-through transcripts in keratinocytes derived from skin stem cells transduced with SIN lentiviral vectors (15). It is thus likely that some degree of vector-induced aberrant splicing always occurs within a population of retrovirally transduced cells and at least a fraction of these cells harbor RNAs generated by 5ʹ or 3ʹ fusion of viral and cellular transcripts ( Figure 1, A and B).…”
Section: Nature's Insolent Unpredictabilitysupporting
confidence: 60%
“…They also found that the presence of a wild-type LTR increased the incidence of aberrant splicing, but since Mavilio and colleagues performed all of their analyses with SIN lentiviral vectors, this nuance gives no real comfort. These findings mirror the recent report of proviral transcriptional read-through transcripts in keratinocytes derived from skin stem cells transduced with SIN lentiviral vectors (15). It is thus likely that some degree of vector-induced aberrant splicing always occurs within a population of retrovirally transduced cells and at least a fraction of these cells harbor RNAs generated by 5ʹ or 3ʹ fusion of viral and cellular transcripts ( Figure 1, A and B).…”
Section: Nature's Insolent Unpredictabilitysupporting
confidence: 60%
“…Conceivably, the mRNAs produced by read-through transcription within vector sequences undergo regulation by the nonsense mRNA decay (18,19,26). As shown in the work of Almarza et al (20), the noncoding transcripts generated by read-through transcription from the internal promoter of an integrated SINLV are regulated by the nonsense mRNA decay mechanism. This would affect the abundance of specific transcripts with respect to all the potential aberrant transcripts that can be generated by all genomic integrations.…”
Section: Discussionmentioning
confidence: 98%
“…These polyadenylation sites, however, are used only in a context-dependent manner and when specific requirements are met (18,19). Moreover, viral-cellular fusion transcripts terminating at cryptic polyadenylation sites located in the host cellular genome were found in keratinocytes transduced with SIN LVs (20). Thus, a complex interplay among the presence, relative strength, position, and distance of promoters; splice site consensus sequences; and mRNA polyadenylation signals is ultimately responsible for the production of specific aberrant mRNAs (17,21).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical studies suggested that the insertion of retroviral splicing and polyadenylation signals within transcription units may cause posttranscriptional deregulation of gene expression with a certain frequency (3,18,21). This may include aberrant splicing, premature transcript termination, and the generation of chimeric, read-through transcripts originating from vector-borne promoters (21), a classical cause of insertional oncogenesis (22). The propensity of LVs to integrate into the body of transcribed genes increases the probability of such events compared with that of MLV-derived vectors.…”
Section: Introductionmentioning
confidence: 99%